Peningkatan Phycocyanin pada Spirulina Platensis dengan Media Limbah Virgin Coconut Oil pada Photobioreactor Tertutup - Sri Sukadarti; Sri Wahyu Murni; M.M. Azimatun Nur (Eksergi, 2016)
Waste of Virgin Coconut Oil (VCO) industries has a high value of Chemical Oxygen Demand (COD), it is therefore a problem for the environment. This waste contains organic materials such as oil, proteins, carbohydrates and some minerals, that potentially to be used for the cultivation of blue-green algae Spirulina plantesis.  Spirulina plantesis is an excellent source of phycocyanin. The Phycocyanin has anti-aging, anti-oxidant and anti-inflammatory properties, it is therefore considered useful. This research is aimed to study the effects of the addition of urea and light intensity on the growth of Spirulina, the concentration of phycocyanin and decreasing of COD value. Spirulina platensis was cultivated in a closed photobioreactor with an air flow for 7 days.  The light intensity was varied as follows 5000 lux, 6000 lux, 7000 lux and 8000 lux, and the addition of urea as nutrients was also varied as follows 40 ppm, 50 ppm, 60 ppm and 70 ppm.  This research indicated that the optimum condition was obtained at the addition of urea of 70 ppm, light intensity  of 6000 lux. This research resulted μmax of 1,1375day-1 , the biomass  productivity of 0,0423 g/l/day,  biomass concentration of   0,1734 g/l  and  phycocyanin concentration of 5,047%. The largest of COD removal is was 98,06% and the COD value of  280 mg/l was finally achieved.